Study of keto-hydrazide crosslinking effect in acrylic latex applied to Portland cements with respect to physical properties - Zarybnicka, Lucie; Pokorny, Jaroslav; Machotová, Jana; Sevcik, Radek; Sal, Jiri; Viani, Alberto (Elsevier Science, 2023)
Polymer-modified Portland-based composites are of interest for specific applications, in reason of their proper-ties. There are different types of commercial additives and waste polymer-based materials applied to cement-based composites, however, their impacts on the environment are debatable. This work has prepared new acrylic latex additives with and without keto-hydrazide crosslinking from standardly available low-cost raw monomers. The influence of their incorporation into Portland cement-based fine-grained mortars has been investigated. The obtained results indicate that the highest effect on heat flow evolution changes has been detected in the case of latexes without crosslinking. The incorporation of both latex types into produced cement composites resulted in a significant increase in open porosity connected with the gradual decrease in mechanical resistance, especially the compressive strength. On the other hand, an important mitigation of liquid water transport properties of latex-modified composites has been achieved, and such properties can be tuned according to the used latex type and its concentration. The developed latex cement-based composites may find utilization as special materials for structures or products for water-loaded constructions or in areas with high concentrations of water-soluble salts or other pollutants.
Studium keto-hydrazidového síťovacího efektu v akrylátovém latexu aplikovaném na portlandské cementy s ohledem na fyzikální vlastnosti
Keywords: Portland cement; Acrylic latex; Keto-hydrazide crosslinking; Water transport properties; Mechanical properties; Portlandský cement; Akrylátový latex; Keto-hydrazidové síťování; Transport vody; Mechanické vlastnosti